COMPETENCY DEVELOPMENT OF EDUCATION ADMINISTRATIVE STAFF AT UNIVERSITAS BRAWIJAYA - Tristanto, Afrendi Hari; Setyowati, Endah; Rozikin, Mochamad (Erudio Journal of Educational Innovation, 2025)
This study examines the development of administrative staff competencies at Universitas Brawijaya, initiated by the increasing demand for responsive and digitally oriented public service in the Society 5.0 era. Despite policy mandates, several challenges persist, including limited functional positions, low creativity, inadequate digital skills, and the absence of an integrated knowledge management system. Using a qualitative approach, data were collected through in-depth interviews, documentation, and observations, and validated through credibility and confirmability techniques. The findings show that competency development is implemented through structured training in digital literacy, data management, public service, and personal development, supported by performance evaluation as a learning mechanism. However, knowledge derived from training and work experience is fragmented and not yet systematically managed. The study concludes that effective competency development requires integrated, continuous, and knowledge-based capacity building aligned with institutional demands for adaptive and high-quality managements.